ANALYSIS OF MARKETING STRATEGIES TO IMPROVE STRENGTHENING THE COMPETITION FOR UMKM - Asrindah Nst; Budiman Purba; Alya Fitria (Universitas Dharmawangsa Medan, 2023)
ABSTRACTMarketing strategy is a measurable approach aimed at making the company’s products known to the general public. Marketing strategy is one way to gain a sustainable competitive advantage either for the company that produces goods or services. Marketing strategies can be used as the basis for preparing the company’s planning. Seeing the problems in the company. So it needs a comprehensive plan that will be used as a guideline for segment companies in conducting their activities, another reason that shows the importance of marketing strategies is the increasingly tight competition of companies in general. The marketing strategy is not only to attract consumers to put the product in the basket, the marketing strategy also ensures that the buyer knows the product offered, verifies and repeats the purchase of the product. Keywords: marketing strategy, competitiveness